2015
DOI: 10.1158/1055-9965.epi-14-1241
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose CT Lung Cancer Screening Practices and Attitudes among Primary Care Providers at an Academic Medical Center

Abstract: Background Low-dose computed tomography (LDCT) screening reduces lung cancer-specific and overall mortality. We sought to assess lung cancer screening practices and attitudes among primary care providers (PCPs) in the era of new LDCT screening guidelines. Methods In 2013, we surveyed PCPs at an academic medical center (60% response) and assessed: lung cancer screening use, perceived screening effectiveness, knowledge of screening guidelines, perceived barriers to LDCT use, and interest in LDCT screening educ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
69
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(80 citation statements)
references
References 22 publications
7
69
3
Order By: Relevance
“…5 Finally, the use of chest radiography remained stable despite its lack of effectiveness in LCS, which may reflect primary care physicians’ knowledge gap regarding the latest scientific discovery in LCS. 6 …”
Section: Discussionmentioning
confidence: 99%
“…5 Finally, the use of chest radiography remained stable despite its lack of effectiveness in LCS, which may reflect primary care physicians’ knowledge gap regarding the latest scientific discovery in LCS. 6 …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that that some PCPs felt that lung cancer screening is not as efficacious as other cancer screening programs such as those for breast or colorectal cancer. 19,20 However based on NLST data, one lung cancer death is prevented with every 320 people screened. 4 This is about equivalent to other cancer screening tests, thus indicating a need for more education among PCPs about the efficacy of lung cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…This process is meant to ensure that the risks, benefits, and limitations of LDCT screening are conveyed to the patient and that the patient has an opportunity to ask questions before deciding to order a screening LDCT. An awareness campaign to motivate patients to approach their health providers about their options for LDCT is an important means of increasing patient engagement, and would help address the concern among providers that a lack of patient knowledge about LDCT presents a major barrier to LDCT screening [9]. …”
Section: Introductionmentioning
confidence: 99%